Particulate lubricants in cosmetic applications - Timm, Katja; Myant, C.; Spikes, H. A.; Grunze, Michael (Tribology international, 2011)
Polymer powders are commonly added to cosmetic formulations to improve product performance and skin feel. This study investigates the effect of particle concentration and size on the lubricating properties of powder suspensions. Results are reported for various particle sizes and concentrations. When the tribological contact was fully immersed the addition of particles had no effect. However different behaviour was observed when the contact was only partially lubricated. In this case, a three-stage friction coefficient curve was observed. By varying the particle size and concentration it was shown that the duration and magnitude of each stage can be controlled.